2008
DOI: 10.1155/2009/909017
|View full text |Cite
|
Sign up to set email alerts
|

FTIR and Thermal Studies on Nylon‐66 and 30% Glass Fibre Reinforced Nylon‐66

Abstract: The present study deals with the characterization of the polymeric materialsviz.,nylon-66 and 30% glass fibre reinforced nylon-66 (GF Nylon-66) by employing FTIR and thermal measurements. The complete vibrational band assignment made available for nylon-66 and GF nylon-66 using FTIR spectra confirm their chemical structure. FTIR spectroscopy provides detailed information on polymer structure through the characteristic vibrational energies of the various groups present in the molecule. The thermal behavior of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(75 citation statements)
references
References 16 publications
6
58
0
2
Order By: Relevance
“…The peaks at 2920 and 2850 cm −1 are related to the CH 2 asymmetric and symmetric stretching vibrations, respectively, whereas the absorption band at 1630 cm −1 was assigned to the amide carbonyl CO stretching vibration of the secondary amide band (amide I). 19 The amide II band at 1540 cm −1 may be attributed to the N−H bending motion and the band at 680 cm −1 to the bending of the OC−N group. 20 After plasma treatment, significant increases in the intensity and broadening of the CO stretching band (as well as of the bending of the OC−N group) were observed.…”
Section: Resultsmentioning
confidence: 99%
“…The peaks at 2920 and 2850 cm −1 are related to the CH 2 asymmetric and symmetric stretching vibrations, respectively, whereas the absorption band at 1630 cm −1 was assigned to the amide carbonyl CO stretching vibration of the secondary amide band (amide I). 19 The amide II band at 1540 cm −1 may be attributed to the N−H bending motion and the band at 680 cm −1 to the bending of the OC−N group. 20 After plasma treatment, significant increases in the intensity and broadening of the CO stretching band (as well as of the bending of the OC−N group) were observed.…”
Section: Resultsmentioning
confidence: 99%
“…5. Amide groups that exist in nylon structure can be recognized in FTIR spectra from peaks located at 1660 and 1541 cm −1 , which correspond to the amide I and II bands, respectively [31]. Detected wavelengths of the dominant bands in the range of 2800-3500 cm −1 originate from the combination of different types of C-H stretching vibrations [32].…”
Section: Physical Properties Of Polymer-coated Nylon Membranesmentioning
confidence: 99%
“…Studies have shown that the science of blending polymers and yet be able to reserve their individual properties in the final blend is a novel and desirable process for developing new structural materials [1][2][3][4] . The mechanical, physical and chemical properties of a polymer are dependent upon the structure and organization of their macromolecules 5,6 . Therefore thorough characterization of the molecular order of a polymer is an imperative undertaking in polymer blend research 7 .…”
Section: Introductionmentioning
confidence: 99%